Gestão sócio-ambiental de empresas de carcinicultura do litoral oeste do estado do Ceará - Costa, Norma Beatriz Camacho (2006)
Shrimp Farming began in Brazil in the 1970s and acquired business characteristics by the end of the 1980s consolidated itselft as a proissory activity in the agribusiness sector. This research aims to analyze the social-environmental management this Shrimp Farming in the west coast of the state of Ceará. This is an exploratory and descriptive study with a qualitative approach developed at eight companies in the sector. The data colletions was carried out by a survey that contains open-ended and multiple choice questions that dealt with the structure of the market and the economic environmental, social results show the weakneses of environmental management of the scrutinized companies. It is possible to realize through the results that the examined companies are not prepared to face the market pressures. Therefore, they need to rethink their management to adequately correspond to the current socialenvironmental demands of the market.